EFL Students' Perceptions about Online Listening Classes as Viewed from the Revised Community of Inquiry (RCoI) Framework - Wijayanti, Erythrina Crista; Widiati, Utami; Tresnadewi, Sintha (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study investigates students' perceptions about online listening classes utilizing the Revised Community of Inquiry (RCoI) framework. Their perceptions were viewed in relation to gender and the learning system used in online listening classes. This survey involved 97 undergraduate EFL Department English students at a state University in Malang. The data were collected through a questionnaire consisting of 33 statements with four scales on the Likert scale. The finding showed that the students positively perceived four presences in RCoI. The analysis also reported that male and female students perceived differently among the presences in RCoI. Moreover, Zoom is the most frequently used in online listening classes. Lastly, some recommendations were also made in this study.